A REVIEW ON FETAL BIOMETRY: MODERN AND AYURVEDIC PERSPECTIVE (International Journal of Ayurveda and Pharma Research, 2016)
The measurements of embryo/fetus are referred to as fetal biometry. Fetal biometric measurements reflect the growth and wellbeing of the fetus during the antenatal period. These parameters aid not only in detecting fetal anomalies but also in estimating the correct gestational age as well as to calculate the estimated date of delivery. The main biometric measurements available in a routine scan report are Crown Rump Length in the first trimester; Bi-parietal Diameter, Head Circumference, Abdominal Circumference, Femur Length in the second and third trimesters. Apart from these primary biometric measurements, secondary fetal parameters can also be assessed on demand. Measurement of parts of human body is referred to as Pramana (measurement) in Ayurveda. The Pramana (measurement) of adult human anatomy is well explained in the Ayurvedic classics under the topic of Pramana Shareera (Anthropometry) but that of Garbha (embryo/fetus) is very vague or almost nil. Details about the stages of growth and development of Garbha (embryo/fetus), it's anomalies, signs and symptoms for the assessment of fetal gender etc. have been vividly narrated in the Ayurvedic classics but the parameters to assess the measurement of Garbha is not at all sufficient to come to a satisfactory conclusion. Here an attempt has been made to explore the Ayurvedic aspects of fetal biometry apart from it's modern review.